Pauls Online Notes
Pauls Online Notes
Home / Calculus I / Limits / Limits At Infinity, Part I
Show Mobile Notice Show All Notes Hide All Notes
Mobile Notice
You appear to be on a device with a "narrow" screen width (i.e. you are probably on a mobile phone). Due to the nature of the mathematics on this site it is best views in landscape mode. If your device is not in landscape mode many of the equations will run off the side of your device (should be able to scroll to see them) and some of the menu items will be cut off due to the narrow screen width.

Section 2-7 : Limits at Infinity, Part I

  1. For \(f\left( x \right) = 4{x^7} - 18{x^3} + 9\) evaluate each of the following limits.
    1. \(\mathop {\lim }\limits_{x \to \, - \infty } f\left( x \right)\)
    2. \(\mathop {\lim }\limits_{x \to \,\infty } f\left( x \right)\)
    Solution
  2. For \(h\left( t \right) = \sqrt[3]{t} + 12t - 2{t^2}\) evaluate each of the following limits.
    1. \(\mathop {\lim }\limits_{x \to \, - \infty } f\left( x \right)\)
    2. \(\mathop {\lim }\limits_{x \to \,\infty } f\left( x \right)\)
    Solution

For problems 3 – 10 answer each of the following questions.

(a) Evaluate \(\mathop {\lim }\limits_{x \to \, - \infty } f\left( x \right)\)

(b) Evaluate \(\mathop {\lim }\limits_{x \to \,\infty } f\left( x \right)\)

(c) Write down the equation(s) of any horizontal asymptotes for the function.


  1. \(\displaystyle f\left( x \right) = \frac{{8 - 4{x^2}}}{{9{x^2} + 5x}}\) Solution
  2. \(\displaystyle f\left( x \right) = \frac{{3{x^7} - 4{x^2} + 1}}{{5 - 10{x^2}}}\) Solution
  3. \(\displaystyle f\left( x \right) = \frac{{20{x^4} - 7{x^3}}}{{2x + 9{x^2} + 5{x^4}}}\) Solution
  4. \(\displaystyle f\left( x \right) = \frac{{{x^3} - 2x + 11}}{{3 - 6{x^5}}}\) Solution
  5. \(\displaystyle f\left( x \right) = \frac{{{x^6} - {x^4} + {x^2} - 1}}{{7{x^6} + 4{x^3} + 10}}\) Solution
  6. \(\displaystyle f\left( x \right) = \frac{{\sqrt {7 + 9{x^2}} }}{{1 - 2x}}\) Solution
  7. \(\displaystyle f\left( x \right) = \frac{{x + 8}}{{\sqrt {2{x^2} + 3} }}\) Solution
  8. \(\displaystyle f\left( x \right) = \frac{{8 + x - 4{x^2}}}{{\sqrt {6 + {x^2} + 7{x^4}} }}\) Solution